2019
DOI: 10.1182/bloodadvances.2018029546
|View full text |Cite
|
Sign up to set email alerts
|

Sporadic and endemic Burkitt lymphoma have frequent FOXO1 mutations but distinct hotspots in the AKT recognition motif

Abstract: FOXO1 has an oncogenic role in adult germinal center–derived lymphomas, in which mutations, predominately within the AKT recognition motif, cause nuclear retention of FOXO1, resulting in increased cell proliferation. To determine the prevalence and distribution of FOXO1 mutations in pediatric Burkitt lymphoma (BL), we sequenced a large number of sporadic and endemic BL patient samples. We report a high frequency of FOXO1 mutations in both sporadic and endemic BL at diagnosis, occurring in 23/78 (29%) and 48/89… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 43 publications
1
28
0
Order By: Relevance
“…Moreover, there is no evidence of a role of FOXO1-activating mutations in BL progression. The clinical outcome of BL does not depend on the FOXO1 mutational status and there is no increase in the frequency of FOXO1 mutations in relapsed cases [44]. This is in clear contrast to DLBCL in which FOXO1 mutations are associated with poor outcome [45,46] and their frequency strongly increases in refractory or relapsed cases [47].…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Moreover, there is no evidence of a role of FOXO1-activating mutations in BL progression. The clinical outcome of BL does not depend on the FOXO1 mutational status and there is no increase in the frequency of FOXO1 mutations in relapsed cases [44]. This is in clear contrast to DLBCL in which FOXO1 mutations are associated with poor outcome [45,46] and their frequency strongly increases in refractory or relapsed cases [47].…”
Section: Discussionmentioning
confidence: 91%
“…EBV infection, which activates PI3K-AKT signalling, indicates a role of PI3K-AKT activation at early stages, but the establishing of BL apparently requires repression of the EBV programme, including PI3K-AKT-and NF-κB-activating LMP genes [8,14,48]. This view is supported by the observation that FOXO1 mutations are found at a significantly higher frequency in endemic BL cases compared with sporadic BL [44]. Thus, frequent FOXO1activating mutations, which confer resistance to the AKTdependent inactivation, might be remnants of the adaptive response to the initial transitory PI3K-AKT activation.…”
Section: Discussionmentioning
confidence: 95%
“…Additionally, an earlier study using tissue samples from 25 Japanese NKTCL patients identified that 3 cases had mutations in the DDX3X gene by conventional Sanger sequencing 21 , while another study in China showed recurrent loss-of-function mutations in DDX3X in 21 out of 105 NKTCL subjects by NGS 11 . In a UK cohort of 78 sporadic BL cases, 15 DDX3X mutations (6 nonsense and 9 missense) were detected, and all but 1 DDX3X mutations were localized in either the DEAD box helicase domain or the helicase C terminus 22 . However, the clinical significance of these lesions remains unclear in most cases.…”
Section: Discussionmentioning
confidence: 99%
“…Available database in the International Cancer Genome Consortium (ICGC) 18 and the Catalogue of Somatic Mutations in Cancer (COSMIC) 19 portals showed mutations in DDX3X in 63 out of 1319 (4.7%) and 160 out of (3.1%) DLBCL cases, respectively. In addition, several other reports that were not in the above databases also demonstrated DDX3X mutations in NHL [8][9][10][11][20][21][22][23][24][25][26][27][28][29][30][31][32][33] . Altogether, we identified 165 missense, 81 truncating, and 3 in-frame indel mutational variants in the DDX3X gene in NHL (Fig.…”
Section: Recurrent Ddx3x Mutations In Nhl Are Associated With Worse Cmentioning
confidence: 99%
“…Surprisingly, FOXO1 knockdown in the MYC-PI3K driven mouse model of BL resulted in cell death and growth arrest [9]. Moreover, FOXO1 gene editing results in time-dependent selection of in-frame edited clones [9] and impedes proliferation of BL cell lines [19], indicating a role of FOXO1 in BL lymphomagenesis.…”
Section: Introductionmentioning
confidence: 99%